Ascorbic Acid Alleviates Damage from Heat Stress in the Photosystem II of Tall Fescue in Both the Photochemical and Thermal Phases - Chen, Ke; Zhang, Minna; Zhu, Huihui; Huang, Meiyu; Zhu, Qing; Tang, Diyong; Han, Xiaole; Li, Jinlin; Sun, Jie; Fu, Jinmin (Frontiers in Plant Science, 2017)
L-Ascorbate (Asc) plays important roles in plant development, hormone signaling, the cell cycle and cellular redox system, etc. The higher content of Asc in plant chloroplasts indicates its important role in the photosystem. The objective of this study was to study the roles of Asc in tall fescue leaves against heat stress. After a heat stress treatment, we observed a lower value of the maximum quantum yield for primary photochemistry (φPo), which reflects the inhibited activity of the photochemical phase of photosystem II (PSII). Moreover, we observed a higher value of efficiency of electron transfer from QB to photosystem I acceptors (δR0), which reflects elevated activity of the thermal phase of the photosystem of the tall fescue. The addition of Asc facilitate the behavior of the photochemical phase of the PSII by lowering the ROS content as well as that of the alternative electron donor to provide electron to the tyrosine residue of the D1 protein. Additionally, exogenous Asc reduces the activity of the thermal phase of the photosystem, which could contribute to the limitation of energy input into the photosystem in tall fescue against heat stress. Synthesis of the Asc increased under heat stress treatment. However, under heat stress this regulation does not occur at the transcription level and requires further study.